Martensitic transformation in free-standing Cu-Al-Ni thin films with micrometric grain size. - Morán M., Condó A. M., Bengio S., Soldera F., Sirena M. and Haberkorn N.; Haberkorn, Néstor (IOP Publishing, 2019)
Fil: Morán, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina